Amplitude analysis and branching fraction measurement of B + → D ∗ − D s + π + decays - Aaij, R; Abdelmotteleb, ASW; Abellan Beteta, C; Abudinén, F; Ackernley, T; Adams, JA; Adefisoye, AA; Adeva, B; Adinolfi, M; Adlarson, P; Agapopoulou, C; Aidala, CA; et al. (Springer, 2024)
The decays of the B+ meson to the final state D∗−Ds+π+ are studied in proton-proton collision data collected with the LHCb detector at centre-of-mass energies of 7, 8, and 13 TeV, corresponding to a total integrated luminosity of 9 fb−1. The ratio of branching fractions of the B+→D∗−Ds+π+ and B0→D∗−Ds+ decays is measured to be 0.173 ± 0.006 ± 0.010, where the first uncertainty is statistical and the second is systematic. Using partially reconstructed Ds∗+→Ds+γ and Ds+π0 decays, the ratio of branching fractions between the B+→D∗−Ds∗+π+ and B+→D∗−Ds+π+ decays is determined as 1.31 ± 0.07 ± 0.14. An amplitude analysis of the B+→D∗−Ds+π+ decay is performed for the first time, revealing dominant contributions from known excited charm resonances decaying to the D*−π+ final state. No significant evidence of exotic contributions in the Ds+π+ or D∗−Ds+ channels is found. The fit fraction of the scalar state Tcs¯0∗2900++ observed in the B+→D−Ds+π+ decay is determined to be less than 2.3% at a 90% confidence level.